PENTINGNYA PENCANTUMAN KETIDAKBERHASILAN UPAYA PERDAMAIAN (DADING) DALAM BERITA ACARA SIDANG DAN PUTUSAN - Agus Pitmantara, Nyoman; Putu Sutama, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013)
The peace effort has an important position in the civil case proceedings in court. This peace effort is done by judges before the examination of lawsuit is implemented. The judges must reconcile the litigants beforehand. Failure of this peace effort must be included in the process verbal and final judgment. Negligence in including failure of peace efforts into the process verbal can cause a civil case in court that contains a formal defect and result in the examination null and void.
Keywords: peace efforts, civil case, court, formal defect, null and void